Gastrostomy tube insertion in pediatric patients with autosomal recessive polycystic kidney disease (ARPKD): current practice - Burgmaier, Kathrin; Brandt, Joy; Shroff, Rukshana; Witters, Peter; Weber, Lutz T.; Dötsch, Jörg; Schaefer, Franz; Mekahli, Djalila; Liebau, Max C. (Frontiers in Pediatrics, 2018)
Introduction Autosomal recessive polycystic kidney disease (ARPKD) is a severe hepatorenal disorder of childhood. Early renal disease in ARPKD may require renal replacement therapy and is associated with failure to thrive resulting in a need for nasogastric tube feeding or gastrostomy. In ARPKD patients, the benefit of a gastrostomy in nutrition and growth needs to be weighed against the potential risk of complications of congenital hepatic fibrosis (CHF) and portal hypertension like variceal bleeding. CHF in ARPKD has thus been considered as a relative contraindication for gastrostomy insertion. Yet, data on gastrostomies in pediatric patients with ARPKD is lacking. Methods We conducted a web-based survey study among pediatric nephrologists, pediatric hepatologists and pediatric gastroenterologists on their opinions on and experiences with gastrostomy insertion in ARPKD patients. Results 196 participants from 39 countries shared their opinion. 45% of participants support gastrostomy insertion in all ARPKD patients, but portal hypertension is considered to be a contraindication by a subgroup of participants. Patient-specific data was provided for 38 patients indicating complications of gastrostomy that were in principal comparable to non-ARPKD patients. Bleeding episodes were reported in 3/38 patients (7.9%). Two patients developed additional severe complications. Gastrostomy was retrospectively considered as the right decision for the patient in 35/38 (92.1%) of the cases. Conclusions This report on the results of an online survey gives first insights into the clinical practice of gastrostomy insertion in ARPKD patients. For the majority of participating physicians benefits of gastrostomy insertion retrospectively outweigh complications and risks. More data will be required to lay the foundation for clinical recommendations.
Gesehen am 30.01.2020